Mental health assistance services: reflections on the challenges of integral health assistance for women - Gazabim Simões Ballarin, Maria Luisa; Ferigato, Sabrina Helena; de Carvalho, Fábio Bruno (O Mundo da Saúde, 2008)
The present work had as its aim to enhance reflections and discussions about integral mental health assistance for women. It is a descriptive, qualitative and narrative survey. LILACS, MEDLINE and SCIELO databases were used as data collection sources. Data analysis showed that in the last decades countless advancements took place regarding public policies directed to integral health assistance for women with an emphasis in mental health. Such policies began to gradually assimilate a gender approach, emphasizing health promotion and integrality. In the mental health field, the priority was the constitution of a network of resources other than traditional psychiatric hospital facilities, aiming at deinstitutionalizing, promoting psychosocial rehabilitation and rescue citizenship for mentally disturbed people. However, even with the observation of these advancements, we identified countless challenges that must still be surpassed, especially when approaching the interface between woman health and mental health, thus requiring a detailed reflection on technical, scientific, ethical and ideological aspects.